Diagnostic, Prognostic and Predictive Biological Markers in Bladder Cancer - Illumination of a Vision - Thorsten Ecke (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue has been introduced with the aim of offering the possibility to publish new research results from old and new pioneers in the field of bladder cancer basic research. While editing this Special Issue we learned that an enormous enthusiasm is necessary to go on in bladder cancer research. In our eyes, bladder cancer is on one hand a very heterogenous malignancy, which is what makes it so difficult to focus on only one bladder cancer marker in bladder cancer diagnostics and follow-up. On the other hand, it is very important to find prognostic and predictive factors for bladder cancer due to its high incidence and its enormous costs, as one of the most expensive malignancies in the world. Finding and developing new bladder cancer markers is still a very dynamic field. Because there are many of these markers, it is impossible to report all of them. This Special Issue attempts to highlight the role of bladder cancer markers in diagnosis, and the most important biomarkers that have been recently studied and reported. This Special Issue highlights some of the most important markers. Further determination of recurrence and progression markers will contribute to establishing better treatments for individual patients. Molecular staging of urological tumors will allow the selection of cases that will require systemic treatment. It is necessary and important to integrate basic and clinical research under the same objectives.